Aspek Penari Dalam Koreografi Kelompok Tari Satu Padu Di Sanggar Belisa Palembang - Lutvi Dwi Samodra; Liza Murniviyanti; Nugroho Notosutanto Arhon Dhony (Jurnal Pendidikan dan Penciptaan Seni, 2022)
The purpose of this study was to determine the dancers' aspects in Satu Padu dance, whether Satu Padu dance has dancer aspects according to the theory used in the study. The theory used in this study is the theory of Y Sumandiyo Hadi regarding the aspects of dancers in group choreography which has 3 elements, namely: 1) Aspects of the number of dancers, 2) Aspects of gender and body posture of dancers, 3) Aspects of the unity of group composition, (a) Aspects of the direction facing the dancers, (b) Aspects of the distance between dancers, (c) Aspects of Key dancers. The research method used is qualitative, this qualitative research method is a method based on philosophy, and this method is used in research with natural object conditions, so this research method is often used by a researcher in an art and culture research. The results of the study are in accordance with the theory used, in this Satu Padu dance, there are dancer aspects according to the dancer aspects of Y Sumandiyo Hadi.